Trade-offs of tropical cover crops: enhanced carbon inputs and soybean yield offset higher N2O emissions - Victória Santos Souza; Mariana Teixeira Borges; Bruna Emanuele Schiebelbein; Lucas Pecci Canisares; Jorge Luiz Locatelli; Larissa de Souza Bortolo; Darliane de Castro Santos; Leandro Pereira Pacheco; Carlos Eduardo P. Cerri; Carlos Eduardo P. Cerri; Maurício Roberto Cherubin; Maurício Roberto Cherubin (Frontiers in Soil Science)
IntroductionIn tropical agriculture, cover crops are increasingly adopted to improve soil health and system resilience. However, their influence on greenhouse gas (GHG) emissions, particularly nitrous oxide (N2O), remains underexplored in field conditions.MethodsWe evaluated how cover crop biomass affects N2O emissions and emission intensity (kg CO2 eq t−¹ grain) in tropical soybean systems across two field experiments (6 and 10 years) in the Brazilian savannah (Cerrado biome). GHG emissions were measured using static chambers on a weekly basis throughout the cropping seasons from 2022 to 2024.ResultsSoybeans followed by cover crops such as MixCC [ruzigrass (Urochloa ruziziensis), millet (Pennisetum glaucum), and showy rattlebox (Crotalaria spectabilis)] and ruzigrass contributed up to 202% more nitrogen and 51% more carbon inputs than soybeans followed by fallow and maize. The cover crop mix emitted ~6,000 kg C ha−¹ as biogenic CO2 in 2 years and 2,655 g N ha−¹ as N2O, ~50%-fold more than the bare fallow. Nevertheless, although high-biomass systems increased N2O emissions during the offseason, they also enhanced soybean yield, leading to lower emission intensity.DiscussionThe structural equation model revealed that cover crop biomass not only had a direct positive effect on soybean yield (standardized coefficient = 0.67) and N2O emissions (standardized coefficient = 0.33) but also an indirect negative effect on emission intensity through yield compensation. These findings suggest that adopting cover cropping systems in tropical regions can efficiently contribute to increasing crop yields while improving nitrogen use efficiency, which is important for food security in these regions.